SAT0433 Application of the doris algorithm for the definition of disease remission over a 2-year period in a cohort of italian patients with systemic lupus erythematosus. (12th June 2018) - Dall'ara, F.; Andreaoli, L.; Armentaro, G.; Migliorati, F.; Frassi, M.; Franceschini, F.; Calza, S.; Tincani, A.
Abstract : Background: Systemic Lupus Erythematosus (SLE) is characterised by a fluctuating course. To achieve sustained remission is the ultimate goal of maintenance treatment. However remission is difficult to define in SLE. In 2014, an international Task Force named DORIS proposed four definitions of remission. 1 Objectives: Aim of this study was to evaluate the performance of the DORIS algorithm in comparison to the remission status as defined by clinical judgement and to identify the frequency of remission as determined by DORIS for each clinical disease pattern. Methods: Monocentric retrospective study. Among all SLE patients followed at the Lupus Clinic between 2014 and 2016, we enrolled patients fulfilling the SLICC 2012 criteria who were visited at least once in 2016 and who had at least 5 biannual medical examinations in the previous 2 years. Definitions of remission according to DORIS, Clinical Remission, and disease patterns are reported in table 1. Results: 101 SLE patients were enrolled for this study (94% female, mean age 45 years). 17.8% of patients were in remission in all the 5 time-points, vice versa 29.7% of patients never got into remission. 17.8% of patients have been in remission for 24 months, while 21.8% of patients less then 6 months. Mean duration of DORIS remission was 7.96 months. The most prevalent disease patter were RR (41, 6%) and CQ (41, 6%), while CA pattern was present in 16, 8% of patients. DORIS remission was most frequently achieved in CQ pattern (65.2% of visits), less frequently in CA (5.9%). 294 visits out of 505 (58%) were defined as "non-remission" according to DORIS. cSLEDAI above zero was the item that most frequently accounted for "non-remission", particularly urinary and haematological (as reported in figure 1). In 229 (43.3%) visits there was a disagreement between DORIS and clinical judgement: the reasons for discordant results were respectively: a) self-management of steroids dosage and precautionary increase of steroids in the suspect of a flare in 7.1%; b) cSLEDAI >0 in 27.2%, PGA≥0.5 in 12.6%, more than one of these items in 53.1%. Conclusions: Nearly 40% of the visits displayed a disagreement between clinical judgement of remission and DORIS remission. This may be attributable mainly to a different approach in evaluating patients: longitudinal by clinical judgement and cross-sectional by DORIS. As compared to clinical judgement of remission, the DORIS definition is not designed to capture "low disease activity", particularly patients who carry a PGA between 0.5 and 1 and those who require a medium dosage of steroids in the frame of a CA pattern. Reference: [1] van Vollenhoven R, et al. Ann Rheum Dis2017Mar;76(3):554–561. Disclosure of Interest: None declared